Comparison of Intrathecal Hyperbaric Bupivacaine Alone and Hyperbaric Bupivacaine with Fentanyl in Lower Limb Surgery - Ghimire, Basanta; Khanal, Kishor; Ghimire, Kundan Kishor; Bajracharya, Anurag (Nepal Journal of Health Sciences, 2024)
Introduction: Subarachnoid block is the preferred anaesthetic technique used for lower limb surgeries because of its rapid and profound sensory and motor blockade. Opioids are widely used in conjunction with local anaesthetics in neuraxial blocks for their property of improving the quality and prolonging the duration of local anaesthetics for surgical anaesthesia, as well as post-operative analgesia. Objectives: Objective of this study was to compare the duration of two segment regression, motor blockade and sensory analgesia, with intrathecal hyperbaric Bupivacaine alone and with Fentanyl added. Method: In this study, 80 patients above 15 years with ASA (American Society of Anaesthesiologist) physical status I and II, undergoing subarachnoid block for various lower limb surgeries were studied in a double-blinded, randomized prospective manner. Patients were divided into two equal groups - Group B (n= 40) received hyperbaric bupivacaine 15 mcg, and Group BF received hyperbaric bupivacaine 12.5 mg with fentanyl 25 mcg, making a total volume of 3 ml in both the groups. Patients were compared intraoperatively and postoperatively for the duration of motor blockade, time for two segment regression and duration of sensory analgesia and complications. Results: The time for two segment regressions, time for sensory analgesia, duration of motor blockade, was significantly higher in group BF i.e., 119 ±19 mins, 310 ±20 mins and 236±17 mins respectively, as compared to group B i.e., 83 ±20, 223 ± 22, 186 ±19 minutes respectively. Both the groups were comparable with demographic profile and hemodynamic parameters. Conclusion: The addition of fentanyl 25 mcg prolongs the time for two segment regression and duration of sensory analgesia for lower limb surgeries.